Nitrogen fertilizer application rate impacts eating and cooking quality of rice after storage. - Hanling Liang (Public Library of Science (PLoS), 2021)
The effect of nitrogen fertilizer application on the quality of rice post-storage is not well understood. The eating and cooking quality (ECQ) of rice treated with 0 (CK, control), 160 (IN, insufficient nitrogen), 260 (AN, adequate nitrogen), and 420 (EN, excessive nitrogen) kg N/ha was analyzed over 12 months of storage. Results showed that the rate of nitrogen fertilizer application had no significant impact on the changes in taste value during storage. However, EN application significantly increased the hardness (p < 0.05), reduced the gumminess (p < 0.05), and delayed the decline in the viscosity of rice paste by two months after one-year storage, compared with other treatments. In conclusion, although EN application resulted in an inferior texture of rice, it delayed the quality change by two months during storage. It was demonstrated that a rational nitrogen application rate (0-260 kg N/ha) for rice cultivation is particularly important to obtain high ECQ; however, EN may be beneficial for the stability of the ECQ during storage.